IBN ATHA`ILLAH AND THE MODERN PHILOSHOPYCAL SUFISM - Sidqi, Ahmad (IAIN Tulungagung, 2019)
Rationalities is being have sufficient as the new god of modern humans. Being the fuel of spirit, they try to negate ?Being? or metaphysical. The impact of it they alienate the social crisis and spiritual crisis. The extremely spiritual crisis generates atheism or at least agnostic. They leaned on the knowledges and technologist which have suspected them as the driving force of modernization process have resulted the higher degree of modern humans? rationality. Instead of losing the beliefs is precisely created the public sphere. The humans modern try to find the spiritual leaned by the Sufism way. One of the interesting Sufism figures to be studied is Ibn Atha`illah. This paper studies about the Ibn Atha`illah?s view in the modern of philosophical Sufism. Practically he was more emphasize the Sufism?s value in ma?rifat view. He is also the main figure of Sufism but his activities or influences was only in it. Ibn Atha`illah was known as the master of Islamic laws in mazhab Maliki and akidah, the competence which as a rule of religious exoteric.